Traditional and Bakul Semanggi Gendong legend phenomenon in surabaya: dynamics and urgency of its preventive extinction (Cogent Social Sciences, 2024)
This article discusses the heritage and traditional cultural study of small-business clover sellers (Bakul Semanggi Gendong) at Surabaya, East Java, Indonesia. Aims to: 1) describe the traditional values of clover carried basket as a micro heritage of culinary business in the city of Surabaya; 2) explore the history of the journey and development of the clover seller from the past to the present. The main relevance provides knowledge to the audience about the importance of maintaining heritage traditions. Implications for scientific discussions in the field of cultural anthropology, including History. Using a naturalistic approach with qualitative, and a focus on ethnographic methods. The subject of this study was a basket of clover carry. The determination of informants is carried out purposive according to predetermined requirements. There are nine informants selling clover, one person from the family, and two customers. The determination of the location of the study was based on the area being the center of clover heritage traditions. Test the validity of the data using triangulation. The results of the study found: 1) The traditional values of the heritage of the clover seller are the scientific capital of the community, as the identity of Surabaya; 2) The history of the journey of the clover seller which is a microeconomic business, its existence still exists today and has developed in terms of how to market, namely by cycling or opening non-permanent booths along Kendung street, Benowo, Surabaya City, Indonesia.